Lourdes Rojas Álvarez, Gramática griega, tomo I: Teoría y tomo II: Ejercicios, México, Herder, 2004, 329 págs., ISBN: 968-5807-03-5 (tomo I); 249 págs., ISBN: 968-5807-04-3 (tomo II); ISBN Obra completa: 968-5807-05 (Minerva. Revista de Filología Clásica, 2019)
Reseña de Lourdes Rojas Álvarez, Gramática griega, tomo I: Teoría y tomo II: Ejercicios, México, Herder, 2004, 329 págs., ISBN: 968-5807-03-5 (tomo I); 249 págs., ISBN: 968-5807-04-3 (tomo II); ISBN Obra completa: 968-5807-05